2021
DOI: 10.1021/acsami.1c17159
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Observation of Temperature-Dependent Defect Evolution within Sub-stoichiometric WO3–x Catalysts

Abstract: Tunable crystalline defects endow WO 3−x catalysts with extended functionalities for a broad range of photo-and electric-related applications. However, direct visualization of the defect structures and their evolution mechanism is lacking. Herein, aberration-corrected and in situ transmission electron microscopy was complemented by theoretical calculations to investigate the effect of temperature on the defect evolution behavior during hydrogenation treatment. Low processing temperature (100−300 °C) leads to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The measured value of 2.004 can be attributed to the oxygen vacancies in the lattice. 36,44 The highest intensity of EPR signal for Pt–WO 3− x indicated that it possesses the largest amount of oxygen vacancies, consistent with the XPS results. In the Raman shift results (Fig.…”
supporting
confidence: 84%
“…The measured value of 2.004 can be attributed to the oxygen vacancies in the lattice. 36,44 The highest intensity of EPR signal for Pt–WO 3− x indicated that it possesses the largest amount of oxygen vacancies, consistent with the XPS results. In the Raman shift results (Fig.…”
supporting
confidence: 84%
“…Moreover, it is clearly to observe that the photocatalytic performance for hydrogen evolution of N‐PHI x gradually increased with the calcination temperature raising from 500 to 600 °C, suggesting that the enhanced charge separation and migration efficiency by introducing more ordered‐distorted interface can improve the photocatalytic water reduction capacity. However, with calcination temperature further increased to 650 °C, N‐PHI 650 catalyst presents clearly decreased photocatalytic water reduction activity, which is probably attributed to the depolymerization of heptazine units [25] . To study the effect of the strong visible light absorption property of distorted heptazine‐based melon structure on the photocatalytic water reduction performance, the activities of N‐PHI 600 at long wavelengths have also been explored.…”
Section: Resultsmentioning
confidence: 99%
“…However, with calcination temperature further increased to 650 °C, N-PHI 650 catalyst presents clearly decreased photocatalytic water reduction activity, which is probably attributed to the depolymerization of heptazine units. [25] To study the effect of the strong visible light absorption property of distorted heptazine-based melon structure on the photocatalytic water reduction perform-…”
Section: Resultsmentioning
confidence: 99%
“…Solar-driven water splitting for hydrogen fuel production using a photoelectrochemical (PEC) platform is an appealing strategy by which to sustain energy demand. [1][2][3][4] In the PEC system, semiconducting photoelectrodes with the properties of the efficient absorption of visible light and high quantum yield have been researched for almost half a century, 5 and a variety of materials, including metal oxides, [6][7][8][9] metal oxynitrides, 10,11 perovskites, 12 polymers, 13 metal-organic frameworks [14][15][16] and other materials, [17][18][19][20][21] have been reported. Among them, conjugated polymers have received broad attention recently.…”
Section: Introductionmentioning
confidence: 99%